Interactions of BDNF Val66met and dietary indices in relation to metabolic markers among patient with type 2 diabetes mellitus: a cross-sectional study - Zeinab Naeini; Faezeh Abaj; Masoumeh Rafiee; Fariba Koohdani (BMC, 2023)
Abstract Background Gene-diet interaction is related to the progression of diabetes and cardiovascular diseases biomarkers. We aimed to evaluate the interaction between diet quality indices and BDNF Val66Mat (rs6265) on cardiometabolic markers among diabetic patients. Methods This cross-sectional study was conducted on 634 patients with type 2 diabetes mellitus, which were randomly recruited from diabetic centers in Tehran. Dietary intakes were estimated by a previously validated semi-quantitative food frequency questionnaire comprising 147 items. All participants were categorized into three categories, based on healthy eating index (HEI), diet quality index (DQI), and phytochemical index (PI) scores. Polymerase chain reaction was used for genotyping the BDNF Val66Met. Interactions were tested using analysis of covariance in adjusted and crude models. Results Our result showed that higher DQI, HEI, and PI scores significantly decrease body mass index and waist circumference among individuals with Met/Met, Val/Met, and Val/Val genotypes (P interactions < 0.05). Moreover, the highest quartile of the DQI and PI, compared to the lowest, showed lower TG level among Met allele carriers compared to Val/Val homozygotes (P interaction = 0.004 and 0.01, respectively) and a faster reduction in IL-18 and TC level was seen among Met/Met, Val/Met who had higher HEI intake than those with Val/Val genotype. Conclusions BDNF Val66Met polymorphism may interact with HEI, DQI, and PI. We have revealed that Met allele acts as a protective allele for diabetic patients and may have a beneficial influence on cardio-metabolic factors through regulating dietary intake.